Living low-training high: Innovative applications and new perspectives on hypoxic interventions for athletes - Goods, P. S. R.; Deldicque, L.; Scott, B: R. (Journal of Sports Sciences, 2025)
The effects of varying degrees of hypoxia on exercise performance have been investigated for many decades (Roskamm et al., Citation1969). In the late twentieth century, living at sea-level but training under hypoxia (which at the time was being referred to as intermittent hypoxic training: IHT) received relatively modest attention in scientific literature. Despite increased attention in the twenty-first century (which by then had been termed live low, train high: LLTH), a review in 2012 concluded that "LLTH does not increase exercise performance at sea level in endurance athletes any more than simply training at sea level" (Lundby et al., Citation2012). A breakthrough occurred in 2013, when Faiss, Léger, et al. (Citation2013) reported improved repeated-sprint performance at sea-level with associated peripheral adaptations following repeated-sprint training in hypoxia (RSH). A review published by the same group that year summarised that, due to "strikingly poor benefits for sea-level performance" following IHT, it was time to turn scientific inquiry towards higher-intensity hypoxic training strategies which are based on "different fundamental mechanisms" (Faiss, Girard, et al., Citation2013). A meta-analysis published only 4 years later vindicated this proposal, demonstrating that RSH induces greater improvement for sea-level repeated sprints than matched training in normoxia (Brocherie et al., Citation2017).